The Role of Quality Assurance in Early Childhood Education Institutions: A Literature Review - adekfera ubbg; rahmattullah; sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Quality assurance in early childhood education institutions plays a pivotal role in shaping the educational landscape for young children aged 0 to 6 years. This literature review aims to investigate the multifaceted role of quality assurance mechanisms across various preschool programs, exploring how these systems contribute to the enhancement of educational practices and the overall development of children. The review synthesizes existing studies that address both theoretical and practical aspects of quality assurance, including standards, assessment tools, and evaluation frameworks. It delves into the importance of adopting a holistic approach that encompasses not only educational outcomes but also social, emotional, and developmental growth. The investigation highlights the correlation between robust quality assurance practices and improved teaching methodologies, effective curriculum implementation, and enriched learning environments that promote child-centered pedagogy. Additionally, the study discusses the challenges faced by educators and administrators in the realm of quality assurance, such as resource constraints, varying stakeholder expectations, and the need for ongoing professional development. It also identifies areas for future research, emphasizing the necessity for a collaborative effort among policymakers, educators, and families in establishing and maintaining quality standards that can lead to sustainable educational practices.